1984
DOI: 10.1152/jappl.1984.56.6.1478
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of hypoxic ventilatory response to exercise performance on Mount Everest

Abstract: At very high altitude, exercise performance in the human sojourner may depend on a sufficient hypoxic ventilatory response (HVR). To study the relationship of HVR to exercise performance at high altitude, we studied HVR at sea level and 5,400 m and exercise ventilation at sea level, 5,400 m, and 6,300 m in nine members of the American Medical Research Expedition to Everest. The relationship of HVR between individuals was maintained when HVR was repeated after acclimatization to 5,400 m (P less than 0.05). Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(72 citation statements)
references
References 35 publications
2
68
1
1
Order By: Relevance
“…Kangchenjunga by MASUYAMA et al (1986). Though this study did not find any relationship between daytime climbing performance and HVR (all climbers reached the summit), the exercise test done at 5,360 m in this expedition revealed that the higher HVR a climber had, the less desaturation during exercise (HASAKO et al, 1988), which agreed with the result of SCHOENE et al (1984). However, we should take cycle time of PB into account.…”
Section: Discussionsupporting
confidence: 76%
“…Kangchenjunga by MASUYAMA et al (1986). Though this study did not find any relationship between daytime climbing performance and HVR (all climbers reached the summit), the exercise test done at 5,360 m in this expedition revealed that the higher HVR a climber had, the less desaturation during exercise (HASAKO et al, 1988), which agreed with the result of SCHOENE et al (1984). However, we should take cycle time of PB into account.…”
Section: Discussionsupporting
confidence: 76%
“…Consequently, the ODC was shifted to the left in hypoxia, improving by 8 percentage units the level of Sao 2 at exhaustion compared with the Sao 2 expected from the ODC corresponding to normoxia (Calbet et al, 2003a). The drop in Sao 2 that occurs with exercise in hypoxia is inversely related to HVR, explaining why sojourners with high HVR may perform better at extreme altitude (Schoene et al, 1984). In addition, replacing the N 2 -O 2 gas mixture by helium-O 2 (both with a Fio 2 ¼ 0.11) allowed increases in V Emax by 31%, Pao 2 by 17%, Sao 2 by 6%, and Vo 2max by 14% (Esposito and Ferretti, 1997), thus emphasizing the impact of hyperventilation on O 2 transport and exercise capacity in hypoxia.…”
Section: Exercise V E In Chronic Hypoxiamentioning
confidence: 95%
“…Ventilation rapidly increases upon acute hypoxic exposure, and this hypoxic ventilatory response (HVR) is generally presumed to enable better performance at altitude by maintaining arterial oxygen saturation levels (Schoene et al, 1984;Masuyama et al, 1986). Alternatively, a strong HVR has also been proposed to be a negative adaptation that reduces ventilatory reserve at altitude (Bernardi et al, 2006), while hyperventilation and the resultant hypocapnia may reduce cerebral blood flow (Poulin et al, 2002;Ainslie and Poulin, 2004).…”
Section: Introductionmentioning
confidence: 99%